2010
DOI: 10.1007/s00280-010-1247-7
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of lipids transporter ABCA1 increases the cytotoxicity of Nitidine

Abstract: These results indicated that NTD efflux is controlled by ABCA1 activity, suggesting that ABCA1 transports molecules other than lipids. Thus, there is a possibility that ABCA1 acts as a drug resistance transporter involved in the cytotoxicity of NTD derivatives. This also suggested that the expression level of the ABCA1 gene may be an indicator for the efficiency of NTD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Our previous study demonstrated that NTD efflux is controlled by the activity of the ABCA1 transporter . CPT treatment in the present study significantly increased the expression of ABCC1, ABCC2, ABCC3 (ABCC1–3) and ABCA1 (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our previous study demonstrated that NTD efflux is controlled by the activity of the ABCA1 transporter . CPT treatment in the present study significantly increased the expression of ABCC1, ABCC2, ABCC3 (ABCC1–3) and ABCA1 (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…NTD accumulation in A549 cancer cells was higher than that in normal WI‐38 cells despite the high expression of ABCC2 or ABCC3 , suggesting that these ABC transporters are not involved in the efflux of NTD. NTD, as well as CPT, is assumed to enter the cells by passive diffusion.…”
Section: Discussionmentioning
confidence: 92%
“…Our previous study identified ATP-binding cassette subfamily A member 1 (ABCA1) as an NTD transporter. ABCA1 is known as a cholesterol transporter [31]. These results suggested that the unique tumor cell selectivity of NTD shown in the present experiment might be supported by various features, such as the efflux activity of ABCB1, ABCA1, and MMP.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies showed that the expression of ABCA1 may be associated with resistance to an antitumor drug. The antitumor activity of nitidine, a benzophenanthridine alkaloid that has antitumor effects via the inhibition of topoisomerase I, was increased upon downregulation of ABCA1 (32). In addition, it was reported that ABCA1 may be related to the resistance to the antitumor activity of curcumin (33).…”
Section: Discussionmentioning
confidence: 97%